Strategic Human Resource Interventions: Assessing the Efficacy of Training and Discipline in the Manufacturing Industry - Muhamad Arief Noor; Halim Tjiwidjaja; Budi Prajogo (Al-Qalam Institute, 2025)
Employee productivity is a critical factor in organizational performance, particularly in the manufacturing sector, where intense competition and operational efficiency demands are driving performance. This study aims to examine the effects of training, work discipline, and job promotion on employee productivity. A quantitative explanatory approach with a survey method was employed. Data were collected from 100 employees selected through simple random sampling using a structured questionnaire measured on a five-point Likert scale. Multiple linear regression analysis was conducted to assess the impact of each independent variable on productivity. The results indicate that training positively and significantly affects productivity (t = 3.436; p < 0.05), as does work discipline (t = 2.498; p < 0.05), while job promotion shows no significant effect (t = -1.005; p > 0.05). Collectively, all three variables have a significant influence on employee productivity. These findings suggest that enhancing productivity in manufacturing organizations is more effectively achieved through strengthening training programs and enforcing work discipline rather than relying solely on promotion policies.